5-Aminolevulinic Acid Thins Pear Fruits by Inhibiting Pollen Tube Growth via Ca2+-ATPase-Mediated Ca2+ Efflux - An, Yuyan; Li, Jie; Duan, Chunhui; Liu, Longbo; Sun, Yongping; Cao, Rongxiang; Wang, Liangju (Frontiers in Plant Science, 2016)
Chemical fruit thinning has become a popular practice in modern fruit orchards for achieving high quality fruits, reducing costs of hand thinning and promoting return bloom. However, most of the suggested chemical thinners are often concerned for their detrimental effects and environmental problems. 5-Aminolevulic acid (ALA) is a natural, nontoxic, biodegradable, and environment-friendly plant growth regulator. One of its outstanding roles is improving plant photosynthesis and fruit quality. Here, results showed that applying 100-200 mg/L ALA at full bloom stage significantly reduced pear fruit set. Both in vivo and in vitro studies showed that ALA significantly inhibited pollen germination and tube growth. ALA decreased not only cytosolic Ca2+ concentration ([Ca2+]cyt) but also "tip-focused" [Ca2+]cyt gradient, indicating that ALA inhibited pollen tube growth by down-regulating calcium signaling. ALA drastically enhanced pollen Ca2+-ATPase activity, suggesting that ALA-induced decrease of calcium signaling probably resulted from activating calcium pump. The significant negative correlations between Ca2+-ATPase activity and pollen germination or pollen tube length further demonstrated the critical role of calcium pump in ALA’s negative effect on pollen germination. Taken together, our results suggest that ALA at low concentrations is a potential biochemical thinner, and it inhibits pollen germination and tube growth via Ca2+ efflux by activating Ca2+-ATPase, thereby thinning fruits by preventing fertilization.